Absence of urinary opioid peptides in children with autism. Issue 9 (12th March 2008) - Cass, H; Gringras, P; March, J; McKendrick, I; O'Hare, A E; Owen, L; Pollin, C
Abstract : Objective: It has been claimed for a number of years that the urine of children with autism contains exogenously derived opioid peptides. This finding is said to reflect a disturbance in the integrity of the gut epithelium, act as a diagnostic marker for autism and predict treatment response to a diet excluding gluten and casein. The aim of the present study was to determine whether exogenous or endogenous peptides were present in the urine of children with autism or of control children. Design: Case-control study Setting: Cases were recruited from two tertiary referral centres specialising in autistic spectrum disorders, while controls were recruited from mainstream primary and secondary schools in the same geographical area. Participants: 65 boys with autism, mean age 7.4 years (range 5–11) and 158 control boys, mean age 7.8 years (range 4.2–11). Investigations: Urine samples were examined by high pressure liquid chromatography (HPLC) and matrix assisted laser desorbtion ionisation-time of flight mass spectrometry (MALDI-TOF MS) for the presence of a number of putative opioid peptides. Outcomes: There were no significant differences between the HPLC urinary profiles of the children affected by autism and the typically developing controls. In those cases where HPLC showed peaks in the locations at which opioid peptides might be expected to be found, MALDI-TOF established that these peaks did not, in fact, represent opioid peptides. Conclusions: Given the lack of evidence for any opioid peptiduria in children with autism, opioid peptides can neither serve as a biomedical marker for autism nor be employed to predict or monitor response to a casein- and gluten-free diet.